IMPACT OF DIGITAL STORYTELLING ON ENGLISH VOCABULARIES DEVELOPMENT IN MULTIMEDIA STUDENTS - Nugrahani, Fitria (LLDIKTI Wilayah X, 2025)
This study examines the impact of digital storytelling on English vocabulary development among multimedia engineering students in an English for Specific Purposes (ESP) context. Using a quasi-experimental pre-test and post-test control group design, the study evaluated the acquisition of 120 technical and academic vocabulary items, focusing on retention and contextual use. The experimental group engaged in digital storytelling activities, while the control group received traditional instruction. The results indicate that digital storytelling significantly improves vocabulary acquisition. The experimental group achieved a 30.5% increase in vocabulary recognition, outperforming the control group’s 19.3% gain. Additionally, students exposed to digital storytelling reported higher levels of engagement and confidence, which were found to positively correlate with vocabulary retention. The integration of multimodal elements-such as visuals, audio, and interactive features-enhanced learning by supporting deeper cognitive processing. These findings suggest that digital storytelling is an effective pedagogical approach for improving vocabulary development and learner motivation in multimedia engineering education. The study highlights its potential as an innovative strategy for ESP instruction, particularly for visually oriented learners in technology-driven environments.